Caracterização física e sensorial do café produzido nas condições topoclimáticas de jesuitas, paraná - Molin, Roberto Natal Dal; Andreotti, Marcelo [UNESP]; dos Reis, André Rodrigues; Furlani Junior, Enes [UNESP]; Braga, Gilberto Costa; Scholz, Maria Brígida dos Santos (My University, 2008)
Climatic variations influence formation and maturation of coffee grains by altering their intrinsic characteristics, which can allow for several types of coffee qualities, including the potential for production of special coffee. This study was carried out to verify the effect of environmental conditions and crop cultivation on chemical composition and their consequences in cup quality of coffees from region of Jesuítas, Paraná State. During the same crop season this study was accomplished (2002-2003), cup quality was evaluated among the producers in several coffee-growing municipalities in Paraná State. It was observed that 86% of samples were classified simply as soft (smooth flavor) or hard (bolder flavor), and 14% were classified as rioysh/rio (strong unpleasant taste). The results concluded that the practices adopted by producers, who have collaborated with the study, reflected positively on the final cup quality, when compared to the overall quality results in the State. The climatic conditions and practices of crop management and harvest in the Jesuitas region made for bolder coffee with low acidity, comparable to high quality coffees produced in Brazil and abroad.
Physical and sensory characterization of coffee produced in the topoclimatic conditions at Jesuítas, paraná state (brazil)
Keywords: Acidity; Coffea arabica; Cup quality